(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Infertility is often caused by congenital anomalies of sexual development and is associated with an unfavorable reproductive prognosis. In recent years, the development of assisted reproductive technologies has significantly improved the reproductive prognosis of infertile patients. Improvement of reproductive prognosis in congenital anomalies of sexual development largely depends on timely diagnosis of anomalies and rational management of patients